2019
DOI: 10.1093/biosci/biy145
|View full text |Cite
|
Sign up to set email alerts
|

From CREATE Workshop to Course Implementation: Examining Downstream Impacts on Teaching Practices and Student Learning at 4-Year Institutions

Abstract: The faculty workshop model has long been used for disseminating innovative methods in STEM education. Despite significant investments by researchers and funding agencies, there is a dearth of evidence regarding downstream impacts of faculty development. CREATE is an evidence-based strategy for teaching science using primary literature. In this study, we examined whether workshop-trained faculty applied CREATE methods effectively and whether their students achieved either cognitive or affective gains. We follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 56 publications
(87 reference statements)
1
22
0
Order By: Relevance
“…Previous studies of the CREATE method have focused on full-semester courses taught by PIs or by faculty who learned and practiced CREATE approaches in multi-day CREATE workshops taught by experienced CREATE practitioners (22)(23)(24). This study demonstrates that a short CREATE module taught by faculty with little CREATE training can also produce some important gains.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Previous studies of the CREATE method have focused on full-semester courses taught by PIs or by faculty who learned and practiced CREATE approaches in multi-day CREATE workshops taught by experienced CREATE practitioners (22)(23)(24). This study demonstrates that a short CREATE module taught by faculty with little CREATE training can also produce some important gains.…”
Section: Discussionmentioning
confidence: 70%
“…We compared students who experienced the CREATE module with those in different sections of the same course taught without CREATE. In this way, we tested the hypothesis that students who experienced a single CREATE module taught over a few class periods would make gains in scientific literacy and selfefficacy while also experiencing positive shifts in epistemological beliefs about scientific skills and knowledge (18)(19)(20)(21)(22)(23)(24). Our hypothesis was partially supported by the data in that students in the CREATE sections made significant gains in self-efficacy but did not gain transferable data analysis skills.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, in our study, course size was not a significant factor in the overall model of teaching practice, and had a very small contribution to our model of RTOP scores over time for FIRST IV faculty. Past research has also found that small course enrollment does not necessarily result in the implementation of learnercentered teaching [4,69,114]. Overall, course infrastructure was more of a perceived barrier for faculty trained in scientific teaching and course size does not seem to have a significant effect on learner-centered teaching practices.…”
Section: Environmental Constraints Have Some Impactmentioning
confidence: 98%